PERENCANAAN PARTISIPATIF DALAM RANGKA PENGENTASAN KEMISKINAN - Nugraha Utama Sudarsana (Universitas Tribhuwana Tunggadewi, 2015)
Daerah Istimewa Yogyakarta has a highest poverty percentage between Java’s provincies. According that situation, since 2012, The Government of Daerah Istimewa Yogyakarta have been creating a poverty aleviation program that called Pilot Village Program of Poverty Alleviation and Food Insecurity. Many of institutions was involved in this program. By using qualitative method, this research tried to describe and analize the poverty and food security aleviation program planning steps that was created by The Government of Daerah Istimewa Yogyakarta in years 2012-2014 also the factors that support as well as obstruct the resident’s participations. The program planning was preceeded by identification of community condition and needs then followed by several planning activities that using the identification data. The resident of pilot village participated to planning process by delivered some feedback within dissemination and monitoring activities. Various community feedback is used to enhance the next period plan. Community participation in program planning is driven by factors the role of stakeholders, public awareness and social systems in the community and on the other side is inhibited by the type of profession and position in society. When we talking about resident’s participation in the program planning process there are still a problems that need to be improved is still marginalization of the poor in decision-making/policy.